(untitled) (Huellas, 2022)
The proposal presented here sought to identify the conceptual and methodological potentialities that are summarized in “Periodistan – An Argentine on the Silk Road”. To do this, we sought to bring closer the author’s perspective and situated experience through his journey to address it from and through an analytical-conceptual framework in as a geographical interpretation. The proposed methodology focused on addressing the author’s stories as an eth-nographic roadmap, to identify the perspective of the inhabitants of distant spaces on the scale of the place. It should be noted that this type of work allows us to approach and understand the (New) Silk Road from a (disorientalized) perspective of the actors who inhabit and experience these territories. The work invites us to get out of the stereotypes and geographic otherness of non-Western territories. The difficulty of approaching distant spaces leads us to present this type of proposal to collaborate with new perspectives on the cultural configurations imposed by the media. In this sense, “Periodistan” allows us to activate our geographical imagination, discovering distant spaces, crossing borders, knowing cultures, dismantling stereotypes, and learning from history.